The Impact of Consolidating On-Demand Food Delivery on Sustainability: A Simulation Study - Sunarso Radhitya V.P.; Wibowo Budhi S. (Logi, 2023)
On-demand food delivery services have transformed the food industry, offering customers a convenient way to order their favorite food from restaurants and have it delivered to their doorstep. However, the increased number of delivery vehicles has led to higher costs, traffic congestion, and carbon emissions. To tackle these negative impacts, consolidating the delivery process by combining multiple orders from different restaurants to various customers has been suggested. This study evaluates the sustainability impact of direct versus consolidated orders in the on-demand food delivery sector. To achieve the objective, we used an agent-based simulation model based on real delivery data from Yogyakarta, Indonesia. Our simulation results indicate that due to constraints in time windows and routing complexity, only a small portion of all orders can be consolidated. But where consolidation is feasible, it can benefit businesses and the environment by reducing costs for customers, increasing drivers’ productivity, and reducing carbon emissions. The downside is that it may result in a longer customer waiting time. These findings provide valuable insights for businesses and policymakers seeking to promote sustainable practices in the on-demand food delivery sector.